Psychological readiness for innovation and individual-style self-regulation of police officers - O. M. Voluiko (Law and Safety)
It has been stressed that very demanding requirements for the effective management activity put forward for the heads of police departments. This activity should ensure the proper performance of professional duties by subordinate employees. The psychological readiness for innovation will allow the representatives of the police leadership to carry out an effective implementation of the strategy of ensuring the protection of individuals and society. The lack of self-regulation makes them vulnerable while taking important professional decisions.